Improved scales of spaces and elliptic boundary-value problems. II - Mikhailets, V. A.; Murach, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We study improved scales of functional Hilbert spaces over $\mathbb{R}^n$ and smooth manifolds with boundary. The isotropic Hörmander-Volevich-Paneyakh spaces are elements of these scales. The theory of elliptic boundary-value problems in these spaces is developed.